Implement cleaner production system to ensure clean oil environment (Field study in Basrah Oil Company / Al-Burgesia Operations association) - ALshibelee, Moslim A.; Naser, Abad Alreda (Journal of Petroleum Research and Studies, 2018)
The research aims to detect the possibility of implementing the Cleaner Production System in the Iraqi Oil Company. Basra Petroleum Company was chosen as a field of study. The check list was distributed to Intended sample of the operation and environment engineers in the AlBargesia Operations association. The research reached a number of results. The weakness of the technical and administrative staff in the company to understand the concepts and practices of cleaner production and clean techniques and how to use them